Analytical technology for cleaning verification and analysis of drug purity in pharmaceutical production. - Corrigan, Damion K. (Cranfield University, 2008)
Production of pharmaceuticals is a complex process which goes beyond the synthetic reactions undertaken to produce the final drug product. In multi purpose manufacturing facilities the equipment used in the processes must be proven to be sufficiently free of residue from the previous compound so that safe manufacture of the next compound can commence. Cross contamination can pose serious health risks so cleaning verification is a process of extreme importance. Pharmaceutical products may contain impurities that originate from the synthetic stages of production, the starting materials or from in situ reactions taking place in the final drug. Some of these impurities may be genotoxic. Genotoxic impurities are a class of impurities for which awareness is currently growing in the pharmaceutical industry. Traditional analytical chemistry methods such as HPLC are currently employed for the detection and quantification of cleaning residues and genotoxic impurities. These methods can be extremely time consuming. The aims of this project are to investigate swab sampling in cleaning verification, to develop alternative analytical methods which speed up and enhance knowledge of the cleaning verification process and to begin the development of an assay system for commonly occurring genotoxic impurities.